Galerie Peter Pakesch Wien 1981-1993. (Wien : Galerie Peter Pakesch, 1993)
Nitsch, Hermann ; Skerbisch, Hartmut ; Renner, Paul ; Rochas, Eugenia ; Tannert, Volker ; Brandl, Herbert ; Obersteiner, Gerald ; Büttner, Werner ; Kippenberger, Martin ; Oehlen, Albert ; Oehlen, Markus ; Wanner, Franz ; Zitko, Otto ; Bretterbauer, Gilbert ; Simoni, Mariella ; Baldessari, John ; Danner, Josef ; Calzolari, Pierpaolo ; Zobernig, Heimo ; Büttner, Werner ; Kienzer, Michael ; Fröhlich, Gertie ; Kosuth, Joseph ; LeWitt, Sol ; Sunkovsky, Beatrix ; West, Franz ; Förg, Gunther ; Baldessari, John ; Herold, Georg ; Iglesias, Cristina ; Kienzer, Michael ; Geiger, Markus ; Vercruysse, Jan ; Clegg & Guttmann ; Huber, Ika ; Zakharov, Vadim ; Rabinowitch, Royden ; Spalletti, Ettore ; Wool, Christopher ; Esterhazy, Mathis ; Kelley, Mike ; Larner, Liz ; Struth, Thomas ; Pistoletto, Michelangelo ; Kabakov, Ilya ; Prina, Stephen ; Balka, Miroslaw ; Malich, Karel
Overzicht tentoonstellingen 1981-1993
boek